MENINGKATKAN KESADARAN TERTIB BERLALU LINTAS DI PERLINTASAN SEBIDANG KERETA API PADA GENERASI MILENIAL (Politeknik Perkeretaapian Indonesia Madiun, 2022)
This activity aims to increase awareness of traffic order among the millennial generation at railroad crossings through socialization of railway safety. This activity is located in Drono Village, Ngawen District, Klaten Regency, Central Java. The participants of this activity are youth who are members of the Drono Village youth association. The material presented was the law of railroad crossings, signs at railroad crossings, traffic rules at railroad crossings, and legal sanctions for violating the rules at railroad crossings. The method used to convey the material is socialization. Participants stated that this activity had increased their understanding and knowledge of railway safety laws. In addition, they are also committed to being an agent of railway safety in their families and communities